Exploring the factors influencing non-Muslim customers towards Islamic banking - Hutomo Danu Saputro (Journal of Entrepreneurial Economics, 2026)
Background:  Indonesia, as the country with the largest Muslim population in the world, implements a dual banking system that accommodates both conventional and Islamic banking. While Islamic banking is rooted in Sharia principles prohibiting interest (riba) and promoting profit and loss sharing its services are increasingly being adopted by non-Muslim customers. This study aims to explore the factors influencing non-Muslim customers’ interest in using Islamic banking services in Indonesia, particularly focusing on product, facility, and promotion aspects. Methods: This research employs a qualitative approach using thematic analysis (TA) to identify recurring themes from interviews, observations, and supporting literature. Data were gathered from non-Muslim customers of several Islamic banks in Indonesia through personal communications and were validated through triangulation and peer review techniques. Findings: The findings indicate that convenience, capital resources, product quality, and facilities are the main determinants influencing non-Muslims to choose Islamic banks. Convenience includes the simplicity of account creation and accessibility of mobile and internet banking services. Capital resources reflect fair and transparent financing schemes based on profit-sharing contracts. Product quality emphasizes trust, ethical investment, and Sharia compliance, while facilities such as mobile banking enhance transactional efficiency and customer satisfaction. Conclusion: In conclusion, Islamic banks in Indonesia are perceived not merely as religious institutions but as inclusive financial alternatives that emphasize fairness, transparency, and technological convenience, making them attractive to both Muslim and non-Muslim customers. Novelty/Originality of this article: The novelty of this study lies in its qualitative exploration of non-Muslim customers’ perceptions of Islamic banking, highlighting non-religious motivations and practical factors often overlooked in previous quantitative research.